Effect of Physical Exercise Under Different Intensity and Antioxidative Supplementation for Plasma Superoxide Dismutase in Healthy Adults: Systematic Review and Network Meta-Analysis - Xu, Yining; Liang, Minjun; Ugbolue, Ukadike C.; Fekete, Gusztáv; Gu, Yaodong (Frontiers in Physiology, 2022)
Background: The dynamic balance between oxidation and anti-oxidation in the body’s internal environment has a significant meaning for human health. Physical exercise and antioxidative supplementation could affect the balance of oxidation and anti-oxidation systems. The evidence on the effects of physical exercise and antioxidative supplementation is mixed. Aims: To identify the effects of physical exercise, antioxidative supplementation, and their combination on the dynamic balance between oxidation and anti-oxidation in different subgroups of healthy adults. Methods: All studies which reported randomized controlled trials with healthy participants were screened and included from the databases of PubMed, Medline, Embase, and Ovid. All participants were reclassified according to their different daily life activities. All physical exercise interventions were reclassified according to the intensity. The effect size would be calculated in percent or factor units from the mean level change with its associated random-effect variance. Result: There were 27 studies included in this review. The agreement between authors by using The Cochrane Collaboration Risk of Bias Assessment Tool reached a kappa-value of 0.72. Maintaining a regular physical exercise routine in an appropriate intensity would be beneficial to the body’s anti-oxidative potential. Anti-oxidative supplementation could have some positive but limited effects on the body’s anti-oxidative status and complex interaction with physical exercise. Conclusion: Keeping a regular physical exercise routine and gradually increasing its intensity according to the individual’s daily life activity might be a better choice to maintain and enhancing the body's antioxidation potential, only using anti-oxidative supplementation is not recommended. More research is needed to explore the best combination protocol.